2013
DOI: 10.1371/journal.pone.0070021
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Casein Kinase 1 in a Minimal Circadian System

Abstract: The Earth’s rotation has driven the evolution of cellular circadian clocks to facilitate anticipation of the solar cycle. Some evidence for timekeeping mechanism conserved from early unicellular life through to modern organisms was recently identified, but the components of this oscillator are currently unknown. Although very few clock components appear to be shared across higher species, Casein Kinase 1 (CK1) is known to affect timekeeping across metazoans and fungi, but has not previously been implicated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 61 publications
3
68
0
Order By: Relevance
“…In all cases, a statistically significant long-period phenotype was observed (Figure 2A,B), associated with an approximately 2-fold overexpression level (Figure 2C). The period lengthening that was observed upon overexpression of CK1 tau was in the same range as that resulting from overexpression of the wild-type CK1 allele (Figure 2D) averaged for 6 independent overexpression lines previously published [18]. This result shows that the effects of both alleles on period lengthening are very similar.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In all cases, a statistically significant long-period phenotype was observed (Figure 2A,B), associated with an approximately 2-fold overexpression level (Figure 2C). The period lengthening that was observed upon overexpression of CK1 tau was in the same range as that resulting from overexpression of the wild-type CK1 allele (Figure 2D) averaged for 6 independent overexpression lines previously published [18]. This result shows that the effects of both alleles on period lengthening are very similar.…”
Section: Resultssupporting
confidence: 82%
“…An initial phase advance is observed upon IC261 treatment, followed by a dose-dependent long period rhythm in the parent line (Figure 3A, B). The period-lengthening effect of IC261 is indeed decreased in CK1 tau -OX21 compared to the CK1-OX line (Figure 3A, C), similarly to the result obtained with overexpression of the wild-type allele (Figure 3A and [18]).…”
Section: Resultssupporting
confidence: 80%
“…Regardless, the data indicate that changes in CK1 activity, perhaps in response to peptidergic signals including PDF or VIP, mediate communication across the circadian network. Intriguingly, a recent study using the unicellular marine alga Ostreococcus tauri indicated that CK1 activity is circadian gated (54), which could also be the case in higher organisms.…”
Section: Ey02910mentioning
confidence: 96%
“…In addition, casein kinase I is a component of fungal clocks (He et al, 2006). An algal clock, which does not require a transcriptional mechanism, is affected by CKI activity (van Ooijen et al, 2013). Cyanobacteria do not have a casein kinase I ortholog, but rhythmic phosphorylation of clock components is the central feature of the circadian mechanism (Nakajima et al, 2005).…”
Section: Introductionmentioning
confidence: 99%